A cell wall-localized glycine-rich protein of dodder acts as pathogen-associated molecular pattern. Issue 1 (1st January 2021) - Slaby, Peter; Körner, Max; Albert, Markus
ABSTRACT: Cuscuta reflexa (giant dodder) is an obligate stem holoparasite withdrawing water, nutrients, and carbohydrates from its hosts. For a broad spectrum of host plants, C. reflexa usually stays unrecognized. The cultivated tomato Solanum lycopersicum, as one notable exception, possesses a leucine-rich repeat receptor protein (LRR-RP), Cuscuta receptor 1 (CuRe1), which enables tomato to recognize C. reflexa as a dangerous parasitic invader and to respond with plant immune responses. During the infection process, a glycine-rich protein (GRP) is freed from C. reflexa and gets detected by CuRe1. Here, we focus on the subcellular localization of the GRP within plant cell walls using a fluorescence based co-localization.